Pet Ownership and Maintenance of Physical Function in Older Adults—Evidence From the Baltimore Longitudinal Study of Aging (BLSA). Issue 1 (25th December 2022) - Friedmann, Erika; Gee, Nancy R; Simonsick, Eleanor M; Barr, Erik; Resnick, Barbara; Werthman, Emily; Adesanya, Ikmat
Abstract: Background and Objectives: Pet ownership or human–animal interaction has been associated with better health outcomes in individuals with disease or disability. We hypothesized that pet ownership, as well as dog ownership and cat ownership separately, are associated with maintaining physical function, and leisure time physical activity and that among dog owners, dog walking is associated with maintaining these outcomes for generally healthy community-dwelling older adults participating in the Baltimore Longitudinal Study of Aging. Research Design and Methods: A total of 637 men (44.1%) and women aged 50–100 years ( M = 68.3, standard deviation [ SD ] = 9.6) completed a comprehensive pet ownership questionnaire that ascertained pet ownership history 10–13 years and had serial assessments of physical function every 1–4 years prior. Linear or generalized linear mixed models with time varying pet ownership were used to examine change in physical function over a mean of 7.5 years (range 1–13, SD = 3.6) according to pet ownership. Results: Pet owners ( n = 185) were significantly younger ( p < .001) and had fewer comorbidities ( p = .03) than nonowners; thus, age and comorbidities were included as covariates in the longitudinal analyses. Physical function and leisure time physical activity declined with aging across all outcomes ( p < .001); the decline was slower among pet owners in overall physical performance ( p < .001), rapid gait speed ( p = .03), usual gait speed ( p = .032), cardiorespiratory fitness ( p < .001), and physical well-being ( p = .002) controlling for age and comorbidities. Changes in leisure time physical activities with aging did not differ between pet owners and nonowners. Dog walking was not independently related to the maintenance of physical function or leisure time physical activity with aging. Discussion and Implications: This study provides the first longitudinal evidence that pet ownership is associated with maintained physical function among community-dwelling generally healthy older adults.